Visible light communication system - Long, Xiao. (2011)
LED lightings are expected to serve in the next generation of lamps. Compared with the conventional lighting methods, white LEDs offer the advantageous properties of lower power consumption, and long lifetime. White LED based indoor lighting systems have been predicted to become the predominant method used for illuminating indoor spaces within the next decade or so.